Mantovani, Dario. Les Juristes Écrivains de la Rome Antique. Les ouvres des juristes comme littérature. Paris: Collège de France-Les Belles Lettres, 2018, 358 pp. ISBN 978-2-251-44813-8 - Rodríguez González, Ana María (ΠΗΓΗ/FONS, 2019)
–